PENGARUH KINERJA PELAYANAN BAPENDA DAN EFEKTIVITAS PENGELOLAAN PENDAPATAN ASLI DAERAH (PAD) TERHADAP PEMBANGUNAN DAERAH (STUDI PERSEPSI WAJIB PAJAK DI KABUPATEN KOLAKA) - Apriani, Icha; Chairunnas, Arnadi; Ilham, Surianto; Nisa, Iien Rohmatin (Jurnal Akuntansi Kompetif, 2026)
The Effect of the Service Performance of the Regional Revenue Agency (BAPENDA) and the Effectiveness of Regional Original Revenue (PAD) Management on Regional Development in Kolaka Regency. Supervisors: Arnadi Chairunnas and Surianto Ilham. This study aims to analyze the effect of the service performance of the Regional Revenue Agency (BAPENDA) and the effectiveness of Regional Original Revenue (PAD) management on regional development in Kolaka Regency. Good service performance of BAPENDA and effective PAD management are expected to improve the financial capacity of the region in supporting regional development. This study uses a quantitave approach with an associative rearch type. The data used are primary data obtained through questionnaires distributed to regional taxpayers in Kolaka Regency who have interacted with the Regional Revenue Agency (BAPENDA).the number of samples in the study was 80 respondents.The data analysis technique used was multiple linear regression analysis with the help of SPSS version 25. The results show that partially the service performance of BAPENDA has a positive and significant effect on regional development in Kolaka Regency. The effectiveness of Regional Original Revenue (PAD) management a and significant effect on regional regional development. Simultaneously, the service performance of BAPENDA and the effectiveness of PAD management have a positive and significant effect on regional development. These results indicate that improving the quality of BAPENDA services and effective PAD management can support regional development and improve community welfare.Keywords: BAPENDA Service Performance, Effectiveness of PAD Management, Regional Development